HAKIKAT KURIKULUM DAN MATERI DALAM PENDIDIKAN ISLAM - Firman Sidik (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2020)
Abstract: This article aims to examine the nature of curriculum and material in Islamic education. The method used in this research is literature review, by studying the theory. The result of this study found curricula and islamic education materials that are relevant and can answer various discussions there. In addition, the education curriculum must be oriented to the preservation of values, orientation to social needs, encourage the workforce, encourage student, and encourage the future and development of science and technology. As well as Islamic education material must be relevant to the needs of human life.Keywords: Curriculum, Material, Islamic Education literature review, by studying the theory. The results of this study found curricula and Islamic education materials that are relevant and can answer various discussions there. In addition, the education curriculum must be oriented to the preservation of values, orientation to social needs, encourage the workforce, encourage students, and encourage the future and development of science and technology. As well as Islamic education material must be relevant to the needs of human life.